2000
DOI: 10.1046/j.1365-2362.2000.00682.x
|View full text |Cite
|
Sign up to set email alerts
|

Microgravity inhibits intestinal calcium absorption as shown by a stable strontium test

Abstract: Intestinal calcium absorption can be diminished after only three weeks of microgravity. Changes are associated with a severe suppression of circulating calcitriol levels, but are independent of exogenous vitamin D supply and serum PTH levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…It takes several weeks after a negative stimulus is given for calcitriol concentrations to decrease to a lower value (23 ). Likewise, it also takes several weeks after a positive stimulus is given for very low calcitriol concentrations to return to the physiological range (31 ), indicating that 1 blood measurement at a specific time point is sufficient to estimate the range in which circulating calcitriol concentrations will be seen over several months. It is an important finding that low circulating calcitriol concentrations also inhibit uptake of 25(OH)D into extrarenal tissues such as monocytes (32 ), indicating that extrarenal calcitriol synthesis is also limited if circulating calcitriol concentrations are low.…”
Section: Discussionmentioning
confidence: 99%
“…It takes several weeks after a negative stimulus is given for calcitriol concentrations to decrease to a lower value (23 ). Likewise, it also takes several weeks after a positive stimulus is given for very low calcitriol concentrations to return to the physiological range (31 ), indicating that 1 blood measurement at a specific time point is sufficient to estimate the range in which circulating calcitriol concentrations will be seen over several months. It is an important finding that low circulating calcitriol concentrations also inhibit uptake of 25(OH)D into extrarenal tissues such as monocytes (32 ), indicating that extrarenal calcitriol synthesis is also limited if circulating calcitriol concentrations are low.…”
Section: Discussionmentioning
confidence: 99%
“…These flight data further documented how increased atrophy of bone mildly increases serum calcium and phosphorus, leading to the reductions in calcium-regulating hormones, to the poor conservation of calcium, and contributing to the negative calcium balance observed with spaceflight [17,25].…”
Section: Presence Of Additional Risk Factors For Bone Lossmentioning
confidence: 78%
“…Although Dumond et al (33) There is controversy over the association between the concentration of 25(OH)D and Ca absorption, which could be carefully extrapolated for Sr. A number of authors have found positive correlations (13,16,21,22,31,34), whereas others have not (15,22,29,35,36). Graff et al (35) found no significant difference in fractional Ca absorption between children with and without active rickets, despite the lower 25(OH)D concentrations in the former group.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies evaluating Sr absorption administered it only with water (6,26,27,28,29,30). Some used a standard breakfast with a known Ca content based on the selection against Sr in favor of Ca in the intestinal tract (8,28,30,31). A standard breakfast was shown to reduce the Sr FAD at each evaluation time as well as the variance within and between subjects, but the shape of the absorption curves remained unchanged (27,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation